VOWEL FORMANT VARIABILITY IN THE SPEECH OF PATIENTS WITH DEMENTIA: A PRELIMINARY ANALYSIS - Gloria Gagliardi; Chiara Meluzzi (Italiano LinguaDue)
The phonetic analysis of speech of patients with dementia has mostly involved durational or supra-segmental features, whereas a minor interest has been dedicated to investigating vowel formant variability. To date, the only studies focusing on vowel variations in speakers with dementia are based on a small Japanese dataset. For this reason, we present here a preliminary investigation on 2 Italian-speaking patients diagnosed with dementia compared with control speakers balanced for all sociolinguistic parameters. The descriptive, static and dynamic analysis mixes a quantitative and qualitative approach. The results show a reduction of vowel space in speakers with dementia, especially along the F1 axis. A more stable vowel contour than the control speakers has also been highlighted. In line with the few previous studies on the topic, these results have been explained as a reduction of tongue movement, in particular on the vertical axis, during speech. These preliminary results represent a fundamental starting point for the creation of a larger dataset of analysis, by balancing pathological speakers, with the associated control speakers, with respect to the typology of dementia and its effect on the subject.